Anodization of large area Ti: a versatile material for caffeine photodegradation and hydrogen production. Issue 16 (7th July 2022) - Sihor, Marcel; Hanif, Muhammad Bilal; Thirunavukkarasu, Guru Karthikeyan; Liapun, Viktoriia; Edelmannova, Miroslava Filip; Roch, Tomáš; Satrapinskyy, Leonid; Pleceník, Tomas; Rauf, Sajid; Hensel, Karol; Monfort, Olivier; Motola, Martin
Abstract : Facile, single-step, and scalable fabrication of large-area (∼20 cm 2 ) TiO2 nanostructures (TNS) with promising photocatalytic activity and hydrogen production rate under UVA light was carried out via electrochemical anodization. Abstract : Facile, single-step, and scalable fabrication of large-area ( i.e., ∼20 cm 2 ) TiO2 nanostructures (TNS) with excellent photocatalytic activity under UVA light was carried out via electrochemical anodization. Anodization in a glycerol-based electrolyte containing fluoride ions was conducted at applied potentials of 20–80 V (20 V per step) for 100 min. Anodization at 20 V (TNS-20) and 40 V (TNS-40) led to formation of nanotubular TiO2, whereas, at 60 V (TNS-60) and 80 V (TNS-80) porous TiO2 was obtained. The highest caffeine photodegradation rate was obtained using TNS-20 (rate constant; k = 0.0069 min −1 ) and TNS-60 (rate constant; k = 0.0067 min −1 ). Moreover, hydrogen production by decomposition of methanol on large-area anodized Ti is reported here for the first time. The highest hydrogen production rate was observed using TNS-20 (production rate of ∼6200 ppm, i.e., 25.83 ppm min −1 ), followed by TNS-60 (production rate of ∼5900 ppm, i.e., 24.58 ppm min −1 ). The efficiency of these two materials is due to the interplay of the structure, morphology, and HO˙ radical generation that favor TNS-20 and TNS-60 for both photocatalysis and hydrogen production. This work shows a potential strategy to synthesize large-area anodic TNS efficient for photocatalysis and hydrogen production. Synthesis of large-area materials is crucial for most real (photo)electrochemical applications where TNS of several cm 2 in macroscopic surface area are necessary.